2017
DOI: 10.5114/biolsport.2017.69823
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation improves economy of movement in the cycle test independently of the detrimental effects of ethanol

Abstract: Taurine (TA) ingestion has been touted as blunting the deleterious effects of ethanol (ET) ingestion on motor performance. This study investigated the effects of ingestion of 0.6 mL·kg-1 of ET, 6 grams of TA, and ethanol in combination with taurine (ET+TA) on economy of movement (EM) and heart rate (HR). Nine volunteers, five female (22 ± 3 years) and four male (26 ± 5 years), participated in a study that used a counterbalanced experimental design. EM and HR were measured for 6 min while the subjects were peda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…The authors found that the ingestion of taurine improved overall endurance performance in the subjects. This conclusion is consistent with the recent findings that taurine is a potential ergogenic aid for preventing muscle damage, attenuating muscle protein catabolism, decreasing oxidative stress, and improving performance in subjects with endurance exercise (De Carvalho et al 2017;Page et al 2019;Paulucio et al 2017;Waldron et al 2019).…”
Section: Health Benefits Of Taurine Supplementationsupporting
confidence: 92%
“…The authors found that the ingestion of taurine improved overall endurance performance in the subjects. This conclusion is consistent with the recent findings that taurine is a potential ergogenic aid for preventing muscle damage, attenuating muscle protein catabolism, decreasing oxidative stress, and improving performance in subjects with endurance exercise (De Carvalho et al 2017;Page et al 2019;Paulucio et al 2017;Waldron et al 2019).…”
Section: Health Benefits Of Taurine Supplementationsupporting
confidence: 92%
“…Indeed, the CP has been described as a 'fatigue threshold' (Poole et al 2016), demarcating a boundary of tolerable exercise intensity. This interpretation is more in keeping with the ergogenic roles of taurine, which are commonly attributed to alterations in fuel utilisation , improved mechanical efficiency (Paulucio et al 2017) or efficiency of ATP turnover in the muscle cell (Hansen et al 2010). Each of these mechanisms has potential to improve exercise tolerance across a range of intensities and could certainly support the 15-W change in CP.…”
Section: Discussionmentioning
confidence: 62%
“…As reported with the above-mentioned acute dietary supplements, taurine supplementation could theoretically alter components of the power-time relationship. For example, aerobically biased (endurance) exercise has typically been improved following taurine supplementation (see Waldron et al 2018a;Souza et al 2017 for reviews) and effects on skeletal muscle function have been reported (Dutka et al 2014;Lim et al 2018), which might collectively explain the improved exercise efficiency following oral administration (Paulucio et al 2017). These mechanistic actions relate to the factors ascribed to govern the balance of CP and W′, which include a loss of muscle efficiency, characterised by distinct metabolic (Jones et al 2008;Vanhatalo et al 2016) and neuromuscular (Burnley et al 2012) profiles.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence to suggest that endurance exercise, performed in thermoneutral environments, can be improved by acute supplementation of taurine (Souza, Del Coso, Casonatto, & Polito, 2017; Waldron, Patterson, Tallent, & Jeffries, 2018b). These benefits have been attributed to increases in muscle function and mechanical efficiency (Balshaw et al, 2013; Paulucio et al, 2017), increased fat oxidation (De Carvalho et al, 2018), as well as enhanced endurance capacity (Waldron, Knight, et al, 2018). We reasoned that these changes should, theoretically, counteract many of the negative effects of cold exposure on exercise efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported an anti‐oxidative effect of taurine supplementation and corresponding increases in aerobic capacity (Zhang, Izumi, Kagamimori, Sokejima, & Yamagami, 2004). These potential effects on muscle contractility and oxidative efficiency or capacity might explain the ergogenic effects elicited by oral taurine supplementation in humans, leading to improvements in maximal muscle force production (Lim, Singh, Leow, Arthur, & Fournier, 2018), endurance (Balshaw, Bampouras, Barry, & Sparks, 2013; Waldron, Knight, Tallent, Patterson, & Jeffries, 2018; Waldron, Patterson, Tallent, & Jeffries, 2018b), or intermittent performance (Warnock, Jeffries, Patterson, & Waldron, 2017), as well as improved exercise efficiency (Paulucio et al, 2017). Indeed, despite some studies demonstrating no overall performance effects of taurine supplementation, the reported increases in fat oxidation rates have indicated enhanced metabolic efficiency and potential for glycogen sparing (De Carvalho et al, 2018; Rutherford, Spriet, & Stellingwerff, 2010).…”
Section: Introductionmentioning
confidence: 99%